Developing Structured Song-Based Learning Materials for English Language Teaching: A Needs Analysis of and Material Prototype Design - Syafira Syafrina Siregar; Jelia Eva Aurelina Simbolon; Emia Ninta Br. Bangun; Anggraini Anggraini; Thesisia Saragih; Khairul Azmi Siagian (BRIGHT VISION, 2026)
This study aims to develop structured song-based learning materials for English language teaching for grade 11 students of SMA Swasta RK Serdang Murni Lubuk Pakam. Utilizing a Research and Development (R&D) method with the ADDIE model, this study integrates songs as authentic learning media into English language teaching. Data collection was conducted through questionnaires and needs analysis involving one English teacher and seventeen students. The findings showed that teachers face difficulties in finding age-appropriate songs, connecting songs with the curriculum, and designing structured activities. Teachers need ready-to-use worksheets, curated song recommendations, and practical teaching guidelines. Students reported difficulties with unfamiliar vocabulary, unclear pronunciation, and fast song tempo. Students prefer pop music with clear lyrics and interactive activities such as karaoke and gap-fill exercises. Based on these findings, a prototype of structured song-based learning materials was developed. The prototype consists of a teacher's guide, student worksheets, and curated song selections. Due to time limits, this study was limited to the needs analysis and design stages of the ADDIE model. The implications suggest that song-based learning materials should include vocabulary support, structured activities that move from listening to speaking tasks, clear guidance for teachers, and song selections that match student preferences while remaining appropriate for classroom use. Future research should conduct expert validation, classroom trials, and effective studies to assess the quality of the prototype.